2001
DOI: 10.1046/j.1526-4610.2001.041007693.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Nasal Sumatriptan in 5‐ to 12‐Year‐Old Children

Abstract: This report demonstrates that nasal sumatriptan may be effective in aborting migraine in young children (aged 5 to 12 years). It also suggests that there may be subgroups for which it works well. This information suggests that double-blind, placebo-controlled studies are necessary to determine the overall effectiveness of nasal sumatriptan in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 7 publications
(13 reference statements)
0
29
0
1
Order By: Relevance
“…in 10 children unresponsive to oral medications, ages 5 -12 years, and treating 57 headaches, reduction of headache severity was demonstrated with sumatriptan 20 mg within 45 min. Sumatriptan was well tolerated, with bad taste being the most frequent complaint [59]. A second study of 14 children under 10 years of age showed a statistically significant response to sumatriptan nasal spray 20 mg for both pain relief (p = 0.03) and pain-free status (p = 0.016) [60].…”
Section: Efficacy In Adolescents and Childrenmentioning
confidence: 99%
“…in 10 children unresponsive to oral medications, ages 5 -12 years, and treating 57 headaches, reduction of headache severity was demonstrated with sumatriptan 20 mg within 45 min. Sumatriptan was well tolerated, with bad taste being the most frequent complaint [59]. A second study of 14 children under 10 years of age showed a statistically significant response to sumatriptan nasal spray 20 mg for both pain relief (p = 0.03) and pain-free status (p = 0.016) [60].…”
Section: Efficacy In Adolescents and Childrenmentioning
confidence: 99%
“…Although the Table II. Nasal sumatriptan data in the pediatric population [12][13][14][15][16][17][18][19] primary endpoints were not met in both of the above studies, [12,13] secondary endpoints showed efficacy for reducing migraine pain and symptoms, and outcomes were similar to those in adult trials.…”
Section: Nasal Sumatriptanmentioning
confidence: 93%
“…[12][13][14][15][16][17][18][19] One study randomized adolescents to sumatriptan 5, 10, or 20 mg nasal spray or placebo for treatment of a single migraine attack. [12] Fifteen percent of the 510 adolescents (12-17 years of age) in the trial used migraine prophylaxis medication.…”
Section: Nasal Sumatriptanmentioning
confidence: 99%
“…Informed consent was obtained from the guardians in the presence of the patient. All guardians were told about the non-FDA indications of all triptans including the references in the literature supporting triptan efficacy and safety in the abortive treatment of migraine in patients aged less than 18 [3][4][5][6][7]. Severity of pain and duration of the attacks were recorded.…”
Section: Methodsmentioning
confidence: 99%